42nd AIAA Aerospace Sciences Meeting and Exhibit 2004
DOI: 10.2514/6.2004-220
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Design of Wings and Wing/Winglet Combinations at Low Speeds

Abstract: Numerical treatment in Prandtl lifting-line theory of the nonlinearity associated with a 2-D lift curve, when the local incidence is larger than the incidence of maximum lift, is proposed. It is shown that the use of an artificial viscosity term makes the solution unique and allows the iterative method to converge to a physically meaningful solution, that is in agreement with the exact solution for the test case. The design and analysis of winglets is presented. The winglets considered are small fences placed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 7 publications
1
26
0
Order By: Relevance
“…Note that the normal force model has historically been used to represent the un-stalled 2D aerofoil lift coefficient of wings operating at high angles of attack within the helicopter and fixed wing aerodynamics literature [34,35]. Later, various models based on the normal force assumption have been widely used to represent the quasi-steady aerodynamics of revolving/flapping wings [15,18,36 -41].…”
Section: Normal Force Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that the normal force model has historically been used to represent the un-stalled 2D aerofoil lift coefficient of wings operating at high angles of attack within the helicopter and fixed wing aerodynamics literature [34,35]. Later, various models based on the normal force assumption have been widely used to represent the quasi-steady aerodynamics of revolving/flapping wings [15,18,36 -41].…”
Section: Normal Force Modelmentioning
confidence: 99%
“…The 2D form of normal force model is expressed as the potential flow model multiplied by a cos a term [34,35]:…”
Section: Normal Force Modelmentioning
confidence: 99%
“…A test case with exact solution, based on the Lifting Line theory and a 2-D lift coefficient given analytically by C l (a) = p sin 2a, has shown that this approach gives excellent results for the complete range of as, from zero to p 2 [10].…”
Section: Algorithm For High-amentioning
confidence: 93%
“…The usability of the current method would be greatly enhanced by additional work on the High-Lift module specifically directed towards modeling wings with powered-lift wings. Some ideas in this area have already been offered by Chattot (58) , and focus primarily on improving the convergence of the solution in cases where the effective angle of attack becomes large.…”
Section: Chapter 8: Conclusion and Recommendationsmentioning
confidence: 99%